2018
DOI: 10.2478/fhort-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Organic N-fertilizer, rhizobacterial inoculation and fungal compost improve nutrient uptake, plant growth and the levels of vindoline, ajmalicine, vinblastine, catharanthine and total alkaloids in Catharanthus roseus L.

Abstract: The aim of the study was to replace mineral fertilizers with organic and biological fertilizers to improve nutrient uptake, plant growth and the concentrations of some important secondary metabolites in periwinkle (Catharanthus roseus L.). Periwinkle plants were grown under different rates of N supply (0, 20 and 40 mg kg -1 soil) and biological treatments (Azospirillum, Azotobacter, Azospirillum plus Azotobacter, Azospirillum plus fungal compost, Azotobacter plus fungal compost, and fungal compost). The concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Monnerat et al [79] found that C. roseus plants supplied with nitrogen fertilizer in combinations with mycorrhizal fungi C. etunicatum, G. margarita and R. intraradices, showed increased production of ajmalicine. Hashemabadi et al [80] reported enhanced level of leaf vindoline (1.94 mg/g DW) and root alkaloid (1.11 mg/g DW) and other plant characteristics by application of 40 mg kg -1 soil nitrogen fertilizer along with Azotobacter and fungal compost. A positively significant effect of plant growth promoting rhizobacteria (PGPR) on the alkaloid content of C. roseus was reported recently [81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Monnerat et al [79] found that C. roseus plants supplied with nitrogen fertilizer in combinations with mycorrhizal fungi C. etunicatum, G. margarita and R. intraradices, showed increased production of ajmalicine. Hashemabadi et al [80] reported enhanced level of leaf vindoline (1.94 mg/g DW) and root alkaloid (1.11 mg/g DW) and other plant characteristics by application of 40 mg kg -1 soil nitrogen fertilizer along with Azotobacter and fungal compost. A positively significant effect of plant growth promoting rhizobacteria (PGPR) on the alkaloid content of C. roseus was reported recently [81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…The separation of the four compounds was achieved by using Diamonsil C18 column (250 mm × 4.6 mm, 5 μm), by using 380 ml solution A [water: diethylamide = 986:14 (v/v), pH 7.2] combined with 620 ml solution B [methanol: acetonitrile = 4:1 (v/ v)] as the mobile phase. The detection was performed at a flow rate of 1.5 ml min-1 and a wavelength of 220 nm within 40 min as described earlier (Hashemabadi et al, 2018).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…According to [26] the application of biological fertilizers containing various N-fixing bacteria can increase the morphological parameters of Catharanthus roseus L as well as secondary nutrient and metabolic absorption. The use of Arbuscular Mycorrhizal Fungi microbes in SRI method rice cultivation can increase SRI method rice production to 13.86 tons ha -1 [27]. Application of Bioorganic Plus containing Trichoderma harzianum and P. fluorescents microbes can increase the SRI method of rice production by 229.05% [28].…”
mentioning
confidence: 99%